12x=11x-23

Simple and best practice solution for 12x=11x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x=11x-23 equation:


Simplifying
12x = 11x + -23

Reorder the terms:
12x = -23 + 11x

Solving
12x = -23 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
12x + -11x = -23 + 11x + -11x

Combine like terms: 12x + -11x = 1x
1x = -23 + 11x + -11x

Combine like terms: 11x + -11x = 0
1x = -23 + 0
1x = -23

Divide each side by '1'.
x = -23

Simplifying
x = -23

See similar equations:

| P-4+6+7p=74 | | 120w+23w=691 | | (-4-7)+1= | | b/13-3b/13=8/3 | | -16+18=-2(x+6) | | -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 | | 9=6(x+6)-7x | | h=160t-16t^2 | | -22-7x=48 | | 4(x-1)-4=2x+2(-3+x) | | u/4=-8 | | 9-0.7k=9 | | 2.37=.87h-.25 | | -5(6+5p)=136 | | -9x-36=90 | | 1+x+7-9x=-24 | | 16x-2=40x+16 | | 22=13+x | | 8a+3(-7)=3 | | -2b/13=8/3 | | a^12=5 | | 54+8x=158 | | (3x+8)=5x | | 6x-9=21+6x | | 18-3y=12 | | 2x-5=2(x-7) | | 30+3x=78 | | 6k^2-42+72=0 |

Equations solver categories